2022
DOI: 10.1038/s42003-022-04341-5
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome-level genome assembly reveals genomic characteristics of the American mink (Neogale vison)

Abstract: Availability of a contiguous chromosome-level genome assembly is the foundational step to develop genome-based studies in American mink (Neogale vison). The main objective of this study was to provide a high quality chromosome-level genome assembly for American mink. An initial draft of the genome assembly was generated using 2,884,047 PacBio long reads. Integration of Hi-C data into the initial draft led to an assembly with 183 scaffolds and scaffold N50 of 220 Mb. This gap-free genome assembly of American mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…It is believed that animals have been intensively under natural selection for several generations due to fatal AMDV infection. Our study prepared the first map of signatures of selection for response to ADMV infection at the chromosome level using WGS data and based on the new gene annotation after the release of the American mink genome assembly at the chromosomal level by Karimi et al 51 . WGS data has already been used to detect selection signals in other domesticated animals, such as pigs 52 and sheep 53 .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that animals have been intensively under natural selection for several generations due to fatal AMDV infection. Our study prepared the first map of signatures of selection for response to ADMV infection at the chromosome level using WGS data and based on the new gene annotation after the release of the American mink genome assembly at the chromosomal level by Karimi et al 51 . WGS data has already been used to detect selection signals in other domesticated animals, such as pigs 52 and sheep 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The GC content around each SNP marker is known to affect the signal strength through the potential interference of genomic waves 36 . Therefore, we first estimated the percentage of GC content of 1-Mb genomic regions surrounding each marker (500 kb on each side) using faToTwoBit and hgGcPercent tools provided by UCSC Genome Browser 37 and the FASTA information of the American mink genome assembly 1 . Next, the GC content file was implemented in PennCNV by ‘-gcmodel’ function, which applies a regression model for adjusting the high GC content and recovers samples affected by genomic waves 38 .…”
Section: Methodsmentioning
confidence: 99%
“…The list of genes in the latest American mink reference genome (ASM_NN_V1) 1 was downloaded from the NCBI and the ‘intersect’ function in Bedtools 45 was used to detect the genes that overlapped with significant CNV regions. Finally, an extensive review of the literature was performed to investigate the biological function of identified candidate genes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations